Mediation of brand reputation and image in the relationship between perceived corporate social responsibility and brand equity and loyalty of technology companies among Generation Z: the moderating role of gender - Jorge Luis Canta Honores; Luciano Barcellos-Paula (Cogent Business & Management, 2024)
This study examines whether the effects of perceived corporate social responsibility (PCSR) on brand equity and brand loyalty are jointly mediated by brand image and brand reputation in the technology industry. It also explores the moderating role of gender in these relationships. The sample consisted of 420 Generation Z members from Lima, selected through gender-stratified random sampling. The study focuses on the technology sector, represented by the large FAANG companies (Facebook, Amazon, Apple, Netflix, and Google), justified by their high stock market visibility and relevance in business strategy research. Data were collected using a 21-item instrument, and PLS-SEM structural equation modeling was employed to explain brand equity and brand loyalty, as well as to validate the items and hypotheses. The results support positive effects between PCSR, brand equity, and brand loyalty, highlighting the previously unexplored mediation of brand image. Additionally, it was found that gender moderates the relationship between PCSR and brand loyalty, with a stronger effect observed among women. The Hierarchy of Effects Model, which examines direct effects, mediators, and moderators, is proposed as the theoretical framework. Practical implications suggest that brand managers should recognize the mechanisms linking PCSR, brand equity, and brand loyalty to effectively attract Generation Z.
Keywords: 650; Perceived corporate social responsibility; brand reputation; brand image; brand loyalty; brand equity; generation Z; technology companies